Social and epistemological preconditions for the formation of security discourse in the history of political and legal thought - Zahumenna, Yuliia (Actual problems of law (Aktual'ni problemi pravoznavstva), 2021)
The aim of the article is to clarify the key social and epistemological preconditions for the formation of security discourse in the history of political and legal thought, which includes the search for the oldest origins of this discourse and patterns of its development in the pre-state era of human civilization. The key research methods are historical, historical-legal, comparative (comparative-legal), systemic, structural-functional, anthropological, etc.Security issues played a key role in the search for optimal ways of survival of human society from the beginnings of early primitive society and in the socio-cultural organization of the primitive community, the ordering and stabilization of social relations. Permeating the entire life cycle of each primitive community, and over time - of each genus, tribe, the desire for a stable and secure existence became the starting point of social construction by people of the surrounding reality. Prerequisites for the emergence of security discourse in the history of political and legal thought should be considered as a set of social and epistemological conditions that allowed the emergence (emergence) of initial rational ideas about the relationship between security and danger in human life, their origin, security and subjects capable of it to ensure, for the further development of these ideas in the development of political and legal doctrines (doctrines) of subsequent historical periods. The formation of such a discourse, in terms of social preconditions, should be interpreted as a natural result of the complexity of social life, its separation from the natural and supernatural worlds, attempts to understand security as real and desirable, in terms of public interest, human protection from internal and external threats. Such preconditions can be considered the emergence of human society with its gradual social differentiation and structuring of subjects and objects of security. The epistemological preconditions of security discourse were the transition from subject-specific to abstract thinking, the formation of the first abstract logical "procategories", which generalized human life experience in the field of desirable, appropriate and safe, understanding the problem of security as universal for natural, social and supernatural (otherworldly) worlds. in the structure of mythological thinking.